2015
DOI: 10.1515/rrlm-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 gene polymorphisms is not associated with drug-resistant epilepsy in Romanian children

Abstract: Background: P-glycoprotein (P-gp)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…In the present, study we did not investigate this polymorphism. In Butila study e TT genotype in position 2677 was more frequently observed in drug-responsive cases (32), which is different from the present data.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present, study we did not investigate this polymorphism. In Butila study e TT genotype in position 2677 was more frequently observed in drug-responsive cases (32), which is different from the present data.…”
Section: Discussioncontrasting
confidence: 99%
“…These differences between studies occurred probably due to a different number of patients included in the studies, the different ethnic populations, and the definition criteria of refractory epilepsy. A previous study performed in a Romanian population had showed an association between TT and CT genotypes in 1236 position with drug-responsive forms in children with idiopathic epilepsy (32). In the present, study we did not investigate this polymorphism.…”
Section: Discussionmentioning
confidence: 63%
“…Consistent with the results of the present study, a Korean study previously reported a non-significant association between the SNPs C3435T, G2677T and T1236C in the MDR1 gene and drug resistance among Korean patients with epilepsy (29). A previous study conducted on Romanian pediatric patients indicated that the T1236C and G2677T polymorphisms of the MDR1 gene were not associated with drug resistance in patients with epilepsy (30). However, the genotypes T1236T, T1236C and T2677T were found to be associated with drug-responsive idiopathic epilepsy (30).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study conducted on Romanian pediatric patients indicated that the T1236C and G2677T polymorphisms of the MDR1 gene were not associated with drug resistance in patients with epilepsy (30). However, the genotypes T1236T, T1236C and T2677T were found to be associated with drug-responsive idiopathic epilepsy (30). Furthermore, another previous study concluded that the T1236C polymorphism in the MDR1 gene was significantly associated with a little to no response to therapy in patients with breast cancer in an Arab population of Saudi Arabia (31).…”
Section: Discussionmentioning
confidence: 94%
“…The genotypes of the investigated MDR1 gene, namely C1236T, G2677T and C3435T gene polymorphisms were established by using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis as previously described by Dong et al and corresponding FastDigest restriction enzyme (namely FastDigest EcoO109I, FastDigest BshNI, FastDigest MboI) supplied by Ther-moFisher Scientific. The PCR conditions were similar to those reported previously (26,27)…”
Section: Genotypingmentioning
confidence: 73%